Investigation of the Relationship between Anxiety Disorder and Time Perception with Perceptional Paradigm - Şan, Hüseyin Oğuzhan; Tarlacı, Sultan; Ulucan, Korkut; Polat, Tolga; Yilmaz, Ozlem Ozge; Aslan, Beste Tacal (Journal of NeuroPhilosophy, 2023)
Anxiety is a pathological condition, as well as a condition that is continued in nature according to the event and situation to keep the vitality alive. For this reason, it is challenging to examine the relationship between the perception of time and the anxiety disease experienced within the limits of normality. Anxiety is one of the most studied topics today. It is also thought that the physical symptoms of anxiety affect cognitive processes. Anxiety, which is observed either alone or in combination with many disorders, shows a possible relationship between the perception of time and some findings related to the subject. These findings show us that people with anxiety disorder have a faster perception of time and a shorter perception estimation. Noticeably more significant differences were found in studies withadolescents. This study used the Beck Anxiety Scale, Zimbardo Time Perspective Inventory, Retrospective and Prospective Time Perception Paradigm, and a Demographic Information Form to collect data. As the variables thought to affect the results of the study were detected in 44 of the 212 randomly selected participants, these participants were excluded from the evaluation, and this study was continued with the data of 168 participants. When the findings are evaluated in general, there is a significant difference between the anxiety scale scores of the sample group and the gender variable. According to this finding, it can be said that the level of anxiety varies between men and women. By looking at the 10, 20, 30, and 40-second video reactions of the participants showing anxiety symptoms; It has been determined that anxiety impairs the time perception of individuals.